Teaching Methods of Basic Piano Courses in Preschool Education in Higher Vocational Colleges - Zhengshan, Xie; Sondhiratna, Thanyawat (Asia Pacific Journal of Religions and Cultures, 2024)
The importance of piano teaching in preschool education majors in colleges and universities cannot be ignored. First of all, as a multi-functional musical tool, the piano has a rich timbre, a wide vocal range and a diverse expressive force. Students majoring in preschool education can better understand and master the principles and methods of children's music psychology and music teaching by learning the piano. Piano teaching can help students to develop good music perception ability and expression ability, and improve their professional quality and educational ability in the field of preschool education. This article presented (1) the teaching methods of basic piano courses in preschool education in higher vocational colleges; (2) optimization of classical teaching methods; (3) methods on measures to improve piano teaching quality in preschool education majors in colleges and universities; (4) the teaching path of piano courses in preschool education major.